Effects of exports instability on economic growth in SAARC region countries - Farhat Rashid; Sami Ullah; Sami Bedi-uz-Zaman Ullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This study analyzed the hypothesis that export instability affects the economic growth for SAARC region countries (Pakistan, India, Sri-Lanka and Nepal) by using neoclassical aggregate production with export and export instability as the additional variables. The Augmented Dickey Fuller (ADF) and Johansson Cointegration tests are used to test stationarity for all variables and cointegration respectively. The results of these tests demonstrate that all variables are non-stationary at levels but stationary at their first difference and co integrated of order I(1). Export instability has deleterious effects for these four countries on economic growth and its magnitude is higher for Sri Lanka economy. The exports and investment has positive and significant effects on economic growth for all countries except the Nepalese economy where export has negative but insignificant effect on its economic growth. The most important policy implications for these countries are that they should diversify their exports horizontally and liberalize their foreign exchange markets and capital accounts to control the instability in exports.
Keywords: 330; Export instability; Growth; ECM; Cointegration; SAARC; Export; Wirtschaftswachstum; Produktionsfunktion; Kointegration; Kointegration; Schätzung; SAARC-Staaten